2017
DOI: 10.1039/c6ra28868e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the surface chemistry of graphene flakes: new strategies for selective oxidation

Abstract: One-step selective oxidation strategies towards the rational tuning of the surface chemistry of graphene flakes are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 74 publications
7
52
0
3
Order By: Relevance
“…The characterization of carbon supports, GF_KMnO 4 and GF_O 3 , by XPS, TPD, FTIR and Raman spectroscopy was previously reported . The reported XPS surface atomic percentages revealed that GF_KMnO 4 presents a higher content in oxygen with a C/O atomic ratio of 4.9, while that of GF_O 3 is 9.8 . The deconvolution of CO 2 and CO evolution TPD spectra showed that both GF_ox materials present a similar low content of carbonyl groups and moderate content of carboxylic acids, carboxylic anhydrides and phenols.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…The characterization of carbon supports, GF_KMnO 4 and GF_O 3 , by XPS, TPD, FTIR and Raman spectroscopy was previously reported . The reported XPS surface atomic percentages revealed that GF_KMnO 4 presents a higher content in oxygen with a C/O atomic ratio of 4.9, while that of GF_O 3 is 9.8 . The deconvolution of CO 2 and CO evolution TPD spectra showed that both GF_ox materials present a similar low content of carbonyl groups and moderate content of carboxylic acids, carboxylic anhydrides and phenols.…”
Section: Resultsmentioning
confidence: 76%
“…The characterization of carbon supports, GF_KMnO 4 and GF_O 3 , by XPS, TPD, FTIR and Raman spectroscopy was previously reported . The reported XPS surface atomic percentages revealed that GF_KMnO 4 presents a higher content in oxygen with a C/O atomic ratio of 4.9, while that of GF_O 3 is 9.8 .…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The oxidized graphene was prepared using a method described by some of us in the literature . Typically 9 mol dm −3 H 2 SO 4 solution was slowly added to a mixture of GF (1.0 g) and KMnO 4 (1.0 g), and the mixture was cooled in an ice bath at 0 °C.…”
Section: Methodsmentioning
confidence: 99%